2014
DOI: 10.1088/0004-637x/797/1/49
|View full text |Cite
|
Sign up to set email alerts
|

The Solar Internetwork. I. Contribution to the Network Magnetic Flux

Abstract: The magnetic network observed on the solar surface harbors a sizable fraction of the total quiet Sun flux. However, its origin and maintenance are not well known. Here we investigate the contribution of internetwork magnetic fields to the network flux. Internetwork fields permeate the interior of supergranular cells and show large emergence rates. We use long-duration sequences of magnetograms acquired by Hinode and an automatic feature tracking algorithm to follow the evolution of network and internetwork flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 36 publications
9
113
0
Order By: Relevance
“…4.3 has been carried out by Lamb et al (2008) based on SOHO MDI magneto-graph data, and by Zhou et al (2010); Wang et al (2012); Lamb et al (2013); Gošić et al (2014Gošić et al ( , 2016 based on Hinode/SOT/NFI data. Their approach differs somewhat from ours in the definition of the events and the type of data used and partly also in the aims of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.3 has been carried out by Lamb et al (2008) based on SOHO MDI magneto-graph data, and by Zhou et al (2010); Wang et al (2012); Lamb et al (2013); Gošić et al (2014Gošić et al ( , 2016 based on Hinode/SOT/NFI data. Their approach differs somewhat from ours in the definition of the events and the type of data used and partly also in the aims of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…This code is applied to time series of high resolution magnetograms obtained in the quiet Sun with the Imaging Magnetograph eXperiment (IMaX, see Martínez Pillet et al 2011) on the Sunrise balloon-borne telescope (see Solanki et al 2010;Barthol et al 2011). The earlier studies using highresolution data to which our results can be compared have used Hinode/NFI data with a spatial resolution of 0 ′′ .3 (6×10 15 Mx, 6.5×10 15 Mx and 5×10 16 Mx being the lowest detected values of flux per feature reported by Zhou et al 2013, Gošić et al 2014and Thornton & Parnell 2011. The higher spatial resolution (a factor of 5 per pixel, see Sect.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, they concluded that the magnetic network was unable to fully relax to its ground state even during the extended period of the last solar cycle around 2009. On the other hand Gošić et al (2014) found that the whole network magnetic field can be sustained, at least during the last extended minimum solar cycle phase, via transported and accumulated weak internetwork fields. Thus the found minimum number and/or the ratio with the maximum number of detected MBPs during the maximum phase can help us, in the future, to estimate the strength of the acting surface dynamo in relation to the global magnetic field dynamo and/or the decaying time constant for the global magnetic fields.…”
Section: Discussionmentioning
confidence: 99%
“…The close spatiotemporal correlation is tempting to infer an intrinsic relation between the RBE and the flux cancellation. This kind of cancellation may be a consequence of magnetic interaction between network and intranetwork fields, as the supergranular convective flows sweep the latter toward the former (e.g., Wang et al 1998;Gošć et al 2014). Later, p2 cancels again with another negative element n2' (Figures 3(h)-(j)), which could be associated with a recurrent RBE event.…”
Section: Rbes Associated With Photospheric Magnetic Flux Emergence Anmentioning
confidence: 97%